Jet lag at the olympics: 24-hour blood pressure profile and time zone transition - Lemmer, Björn; Nold, Gudrun; Kern, Ralph-Ingo; Lohrer, Heinz (Biologic effects of light 1998, 1999)
There is only limited information whether and to what an extent time zone transition can influence the 24-hour blood pressure profile in humans. Blood pressure data after transmeridian flights were only published from occasional blood pressure measurements. Thus, it was the aim of the present study to investigate the effects of an eastward and a westward transmeridian flight on 24-hour profiles of blood pressure and heart rate by ambulatory BP monitoring in top athletes of the German Olympic team participating in the Olympic Games at Atlanta, USA.